Age and growth of bull ray Aetomylaeus bovinus (Chondrichthyes: Myliobatidae) from the northeastern Mediterranean coast of Turkey - Basusta, Nuri; Aslan, Ergun (Cahiers de Biologie Marine, 2018)
Age and growth estimates were determined for the first time in bull ray Aetomylaeus bovinus (E. Geoffroy Saint-Hilaire, 1817) (Chondrichthyes: Myliobatidae) from the northeastern Mediterranean coast of Turkey. A total of 94 bull rays ranging from 29.5 to 129.2 cm disc width and weighing 0.27-33.60 kg. They were collected as by-catch by commercial fishermen using trawls and purse-seines, between September 2010 and December 2012. The sample comprised 50% of females and 50% of males. Maximum age was 14 years for females. The relationship disc width versus body mass (W) relationship was determined as W = 0.05815 x DW2.94. Growth parameters of the von Bertalanffy equation were: DW infinity = 242.59 cm, k = 0.056 year(-1) and t(0) = -1.904 year for females and DW infinity = 238.43 cm, k = 0.044 year(-1) and t(0) = -2.982 years for males.
Keywords: Bull Ray; Aetomylaeus bovinus; Age Determination; Growth Models; Mediterranean Sea